Expected shortfall in the presence of asymmetry and long memory: An application to Vietnamese stock markets. Issue 2 (3rd April 2017) - Walther, Thomas
Abstract : Purpose: This study aims to analyse the conditional volatility of the Vietnam Index (Ho Chi Minh City) and the Hanoi Exchange Index (Hanoi) with a specific focus on their application to risk management tools such as Expected Shortfall (ES). Design/methodology/approach: First, the author tests both indices for long memory in their returns and squared returns. Second, the author applies several generalised autoregressive conditional heteroskedasticity (GARCH) models to account for asymmetry and long memory effects in conditional volatility. Finally, the author back tests the GARCH models' forecasts for Value-at-Risk (VaR) and ES. Findings: The author does not find long memory in returns, but does find long memory in the squared returns. The results suggest differences in both indices for the asymmetric impact of negative and positive news on volatility and the persistence of shocks (long memory). Long memory models perform best when estimating risk measures for both series. Practical implications: Short-time horizons to estimate the variance should be avoided. A combination of long memory GARCH models with skewed Student's t -distribution is recommended to forecast VaR and ES. Originality/value: Up to now, no analysis has examined asymmetry and long memory effects jointly. Moreover, studies on Vietnamese stock market volatility do not take ES into consideration. This study attempts to overcome this gap. The author contributes by offering more insight into the Vietnamese stock market properties and shows the necessity of considering ES in risk management. The findings of this study are important to domestic and foreign practitioners, particularly for risk management, as well as banks and researchers investigating international markets.